STRATEGI KOMUNIKASI YAYASAN BALI PEDULI DALAM MENGEDUKASI MASYARAKAT TERHADAP PENCEGAHAN HIV/AIDS PADA PEREMPUAN - Pratiwi, Ketut Alit; Pascarani, Ni Nyoman Dewi; Pradiptha, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT HIV / AIDS has become a common problem not only in Indonesia but worldwide. HIV / AIDS can attack anyone, including women. Lack of communication, information and education makes also women one of the groups vulnerable to contracting as well as groups that can also transmit HIV / AIDS. In addition, women also experience social problems such as getting negative stigma and discrimination from the surrounding environment. The Bali Peduli Foundation is a non-profit social foundation that handles HIV / AIDS issues. This type of research is descriptive qualitative. This research uses interviews, observation and documentation for data collection. The results of the research conducted at the Bali Peduli Foundation are prevention and mitigation. The Bali Peduli Foundation distinguishes its audience before being educated in preventing and controlling the community regarding HIV / AIDS in women. Keywords: HIV / AIDS, Bali Peduli Foundation, Women, Education